APOE Allele Frequency in Southern Greece: Exploring the Role of Geographical Gradient in the Greek Population - Papastefanopoulou,V.; Stanitsa,E.; Koros,C.; Simoudis,A.; Florou-Hatziyiannidou,C.; Beratis,I.; Antonelou,R.; Andronas,N.; Voskou,P.; Angelopoulou,E.; Papatriantafyllou,J.D.; Stefanis,L.; et al. (Geriatrics (Basel), 2022)
BACKGROUND: the apolipoprotein e4 allele (APOE4) constitutes an established genetic risk factor for Alzheimer's Disease Dementia (ADD). We aimed to explore the frequency of the APOE isoforms in the Greek population of Southern Greece. METHODS: peripheral blood from 175 Greek AD patients, 113 with mild cognitive impairment (MCI), and 75 healthy individuals. DNA isolation was performed with a High Pure PCR Template Kit (Roche), followed by amplification with a real-time qPCR kit (TIB MolBiol) in Roche's Light Cycler PCR platform. RESULTS: APOE4 allele frequency was 20.57% in the ADD group, 17.69% in the MCI group, and 6.67% in the control group. APOE3/3 homozygosity was the most common genotype, while the frequency of APOE4/4 homozygosity was higher in the AD group (8.60%). APOE4 carrier status was associated with higher odds for ADD and MCI (OR: 4.49, 95% CI: [1.90-10.61] and OR: 3.82, 95% CI: [1.59-9.17], respectively). CONCLUSION: this study examines the APOE isoforms and is the first to report a higher APOE frequency in MCI compared with healthy controls in southern Greece. Importantly, we report the occurrence of the APOE4 allele, related to ADD, as amongst the lowest globally reported, even within the nation, thus enhancing the theory of ethnicity and latitude contribution
Keywords: Blood